2020
DOI: 10.1556/2006.2020.00008
|View full text |Cite
|
Sign up to set email alerts
|

Response trajectories of gambling severity after cognitive behavioral therapy in young-adult pathological gamblers

Abstract: Background and aims The significant increase in the prevalence of gambling disorder (GD) among young adults in recent years has attracted interest in determining therapeutic efficiency in this sector of the population. The aim of this work was to estimate the response trajectories of gambling severity during the six-month follow-up after a cognitive behavioral therapy (CBT) program in young adult patients and to identify the main variables associated with each trajectory. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…Interestingly, only a low self‐directedness was significantly associated with more deficits in decision making, and this low neuropsychological performance mediated the relationship between self‐directedness and bad outcome. Self‐directedness indicates the ability to regulate and adapt behaviour to the demands of a situation in order to achieve personally chosen goals and values (Cloninger, 1999), which, according our results, influences the decision making process, and, as has been mentioned in the literature, it is related with difficulties in following therapy goals and achieving a good treatment outcome in BSD and other BA (Fernández‐Aranda et al., 2021; Granero et al., 2020; Wagner et al., 2015). Also, the path‐analysis showed that deficits in cognitive flexibility were positively associated with the presence of the comorbidity.…”
Section: Discussionsupporting
confidence: 55%
“…Interestingly, only a low self‐directedness was significantly associated with more deficits in decision making, and this low neuropsychological performance mediated the relationship between self‐directedness and bad outcome. Self‐directedness indicates the ability to regulate and adapt behaviour to the demands of a situation in order to achieve personally chosen goals and values (Cloninger, 1999), which, according our results, influences the decision making process, and, as has been mentioned in the literature, it is related with difficulties in following therapy goals and achieving a good treatment outcome in BSD and other BA (Fernández‐Aranda et al., 2021; Granero et al., 2020; Wagner et al., 2015). Also, the path‐analysis showed that deficits in cognitive flexibility were positively associated with the presence of the comorbidity.…”
Section: Discussionsupporting
confidence: 55%
“…Previous reports have outlined that low TCI-SD scores are associated with addictive disorders (Anghelescu et al, 2010;Cowie et al, 2019;Gierski et al, 2017;Kovacs et al, 2020;Steingrimsson, Carlsen, Lundstrom, Lundstrom, & Nilsson, 2020), including GD (Claes et al, 2012;Janiri, Martinotti, Dario, Schifano, & Bria, 2007;Moragas et al, 2015;Nordin & Nylander, 2007). However, to our knowledge, only a few studies have explored the role of the selfdirectedness dimension in the course of the disease (Aragay et al, 2015;Granero et al, 2020;Jimenez-Murcia et al, 2015). In particular, it was found that individuals with low TCI-SD scores were at risk of poor outcomes six months after the end of treatment (Granero et al, 2020).…”
Section: Resultsmentioning
confidence: 94%
“…However, to our knowledge, only a few studies have explored the role of the self-directedness dimension in the course of the disease ( Aragay et al, 2015; Granero et al, 2020; Jimenez-Murcia et al, 2015 ). In particular, it was found that individuals with low TCI-SD scores were at risk of poor outcomes six months after the end of treatment ( Granero et al, 2020 ). Our study is the first to suggest the influence of a high TCI-SD score on sustained recovery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, three out of the 34 studies had medical interventions (Memantine; Grant et al, 2010a ; Disulfiram; Mutschler et al, 2010 ; Naltrexone; Ward et al, 2018 ). The most reported psychotherapeutic interventions were cognitive behavioral therapy (CBT, n = 10: Castren et al, 2013 ; Rossini-Dib et al, 2015 ; Tarrega et al, 2015 ; Boughton et al, 2016 ; Smith et al, 2016 , 2018 ; Bouchard et al, 2017 ; Mallorqui-Bague et al, 2018 ; Zhuang et al, 2018 ; Granero et al, 2020 ), which was delivered either in groups or individually, either face to face (F2F) or digitally. This was followed by motivational interviewing (MI, n = 4: Grant et al, 2011 ; Parhami et al, 2012 ; Pasche et al, 2013 ; Stewart et al, 2016 ), mindfulness based interventions ( n = 3: de Lisle et al, 2011 ; Shead et al, 2020 ; van der Tempel et al, 2020 ), dialectical behavior therapy (DBT, n = 1: Christensen et al, 2013 ), acceptance and commitment therapy (ACT, n = 1: Nastally and Dixon, 2012 ), and transcranial magnetic stimulation (TMS, n = 1: Zack et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%